PENGARUH OPINI AUDIT, SOLVABILITAS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Kasus pada Perusahaan Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia) - Kurniati, Afifah; Tabrani, Mr.; R, Dien Noviany (PERMANA, 2017)
His research was conducted to examine the effect of audit opinion, solvency and institutional ownership both partially and simultaneously on the timeliness of submission of financial reports to basic industrial and chemical companies listed on the Indonesia Stock Exchange during the 2014-2016 period. The research method in this study uses quantitative methods. The sampling technique in this study used a Pusposive sample and produced 38 companies. The analysis used in the study used logistic regression because the dependent variable in this study used dummy.The results of this study indicate that audit opinions and solvency partially do not affect timeliness. Meanwhile, institutional ownership partially affects the timeliness. Simultaneously, audit opinion, solvency and institutional ownership variables influence the timeliness of financial statement submission. Keywords: Timeliness, audit opinion, solvency (slovability), institutional ownership